2023
DOI: 10.3389/fphys.2023.1074160
|View full text |Cite
|
Sign up to set email alerts
|

The mechanisms of potassium loss in acute myocardial ischemia: New insights from computational simulations

Abstract: Acute myocardial ischemia induces hyperkalemia (accumulation of extracellular potassium), a major perpetrator of lethal reentrant ventricular arrhythmias. Despite considerable experimental efforts to explain this pathology in the last decades, the intimate mechanisms behind hyperkalemia remain partially unknown. In order to investigate these mechanisms, we developed a novel computational model of acute myocardial ischemia which couples a) an electrophysiologically detailed human cardiomyocyte model that incorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 93 publications
0
5
0
1
Order By: Relevance
“…Regional acute myocardial ischaemia was modelled in human 2D and 3D tissues including the (i) core ischaemic zone (CZ), (ii) lateral border zone (BZ), and (iii) endocardial BZ. 15 Ischaemia was modelled as circular/spherical with a diameter of 5 cm (including CZ and BZ), 12 , 15 , 16 , 27 consistent with reported concentric perfusion defects in HCM, 28 which are frequently >3 cm in extent. 29 The lateral BZ was modelled as 0.5 cm in width, and the endocardial BZ was modelled as 0.06 cm in width.…”
Section: Methodsmentioning
confidence: 68%
“…Regional acute myocardial ischaemia was modelled in human 2D and 3D tissues including the (i) core ischaemic zone (CZ), (ii) lateral border zone (BZ), and (iii) endocardial BZ. 15 Ischaemia was modelled as circular/spherical with a diameter of 5 cm (including CZ and BZ), 12 , 15 , 16 , 27 consistent with reported concentric perfusion defects in HCM, 28 which are frequently >3 cm in extent. 29 The lateral BZ was modelled as 0.5 cm in width, and the endocardial BZ was modelled as 0.06 cm in width.…”
Section: Methodsmentioning
confidence: 68%
“…The likely mechanisms that can explain her transient short QT interval following her tachyarrhythmia include multiple considerations. First, a wide variety of transient metabolic changes occur during ventricular tachyarrhythmias, including increased myocardial intracellular calcium from supply‐demand mismatch, transient acidosis, and elevated serum potassium from tissue ischemia 7 . Additionally, the VR response to changes in heart rate (HR) has also been demonstrated to be maladaptive in patients with LQTS.…”
Section: Discussionmentioning
confidence: 99%
“…Her genetic test showed LQT2 with a mutation of KCNH2 gene. 7 Additionally, the VR response to changes in heart rate (HR) has also been demonstrated to be maladaptive in patients with LQTS.…”
Section: Case Reportmentioning
confidence: 99%
“…Among the chosen biomarkers, we picked potassium for screening analysis, considering the inherent importance of electrolytes in diagnostics and the clinical role of potassium as a health indicator [12,13,[51][52][53][54][55][56]. Furthermore, several studies have been performed using nextgeneration platforms, showing the differential expression of biomarkers, including omic biomarkers or protein and gene expression of these biomarkers and others related to potassium, in the context of mortality or cardiac complications [57][58][59][60][61][62][63][64][65].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies revealed a connection between high potassium levels and myocyte ischemia [ 12 , 13 ], which triggers an imbalance of potassium levels, numerous inflammatory markers in the arrhythmogenesis pathway, and damages the myocardium that results in myocarditis and arrhythmias in COVID-19 [ 14 ]. Additional studies have shown that COVID-19 patients with high troponin T levels are at elevated risk for the development of severe disease, mortality, and require ICU admission [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%